(untitled) (SS Multidisciplinary Research Journal, 2025)
Nepal strives to achieve the Sustainable Development Goals (SDGs). This commitment requires the assessment of the existing economic, social, and environmental dynamics to ensure that development is both inclusive and sustainable. Despite the urgent call for action, the factors affecting sustainable development are not adequately studied. This paper aims to analyze the economic aspects by identifying the effects of key economic variables on sustainable development. Specifically, the research empirically examines the impacts of nonrenewable energy consumption, government size, financial development, urban population, and interest rate on Adjusted Net Savings (ANS) recognized by the World Bank as an indicator of sustainable development. The research employs an ARDL bounds testing approach to cointegration on annual data for Nepal from 1994 to 2021. The data are sourced from the publications of the World Bank, the International Energy Agency and Nepal Rastra Bank. The result of the ARDL bounds test confirmed the existence of cointegration. Further, the estimated long-run coefficients of the ARDL model indicate a negative and statistically significant effect of energy consumption and financial development on ANS. Government size has a positive impact. However, the urban population and interest rate are negative but insignificant. Nepal should make productive energy use through manufacturing, promote hydropower as a sustainable energy source and implement regulations for financial institutions to encourage productive investments and discourage unproductive consumption. Additionally, the government should allocate funds toward sectors like infrastructure, education, agriculture, and renewable energy sources to promote long term sustainable growth.